ANALYZING ARGUMENTATIVE WRITING OF EFL UNIVERSITY STUDENTS - Dagang, Antonius Gabriel Padu; Djehatu, Maria Goreti; Lomi, Aplonia Nelci Ke; Toni, Elvis Albertus Bin; Lake, Floribertha (ENGLISH, 2025)
This study sought to analyze how the third-semester students of the English Education Study Program of Widya Mandira Catholic University structured their writings based on the generic structures and language features of argumentative writing. A qualitative descriptive method was used in this study. The findings revealed the most common problem was the absence of counterarguments, which was found in the writings of 24 students (80%). There was also a problem of merging the generic structures, which was done by 14 students (46.67%). In correlation to this, 11 students (36.67%) contained weak and unclear conclusions in their writings. Another problem found was the lack of formal tone, where 13 students (43.33%) still used casual and informal phrases, and they showed subjective and informal attitude towards the topics. Errors of omission, addition, misformation, and misordering were also found in 14 students’ writings (46.67%). Misformation was the most frequently found with the total of 28 errors (45.16%), followed by omission with the total of 24 errors (38.71%), addition with the total of 7 errors (11.29%), and misordering with the total of 3 errors (4.84%), These findings suggest that simply assigning argumentative essays is not enough and there need to be more explicit guidance in structure, academic style, as well as grammar.